2018
DOI: 10.1007/s00421-018-3925-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the two-point method applied in field conditions for routine testing of muscle mechanical capacities in a leg cycle ergometer

Abstract: These results support the two-point method as a reliable, valid, and fatigue-free procedure of assessing the muscle mechanical capacities through the F-V relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 25 publications
2
23
2
Order By: Relevance
“…The two-point method was proposed by Jaric (2016) to simplify the testing procedure of the F-V relationship. Previous studies have confirmed that the two-point method can provide reliable and valid F-V relationship parameters in different exercises (Garcia-Ramos, Zivkovic, et al, 2018;Garcia-Ramos & Jaric, 2018a;Grbic et al, 2017), including vertical jumps (Garcia-Ramos, Pérez-Castilla, et al, 2018;Zivkovic et al, 2017). However, this is the first study that has applied the two-point method under field conditions (i.e., only two loads applied) to determine the F-V relationship during vertical jumps.…”
Section: Discussionmentioning
confidence: 84%
“…The two-point method was proposed by Jaric (2016) to simplify the testing procedure of the F-V relationship. Previous studies have confirmed that the two-point method can provide reliable and valid F-V relationship parameters in different exercises (Garcia-Ramos, Zivkovic, et al, 2018;Garcia-Ramos & Jaric, 2018a;Grbic et al, 2017), including vertical jumps (Garcia-Ramos, Pérez-Castilla, et al, 2018;Zivkovic et al, 2017). However, this is the first study that has applied the two-point method under field conditions (i.e., only two loads applied) to determine the F-V relationship during vertical jumps.…”
Section: Discussionmentioning
confidence: 84%
“…This method currently appears as the best alternative to the standard force plate measurements in terms of time efficiency, fatigue avoidance and safety. The interest of various two-point methods for F-V profiling is rapidly increasing for other movements as well, with important methodological advances recently being made for cycling 35 and bench press exercise 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The intercepts with force axis and velocity axis were calculated to determine the predicted force in isometric conditions (F 0 ) and maximal theoretical velocity (V 0 ), respectively. The F-v profile was calculated as the slope of the F-v linear relationship, using the following equation 25,26,35 : Finally, the theoretical maximal power (P max ) was calculated as in the previous F-V studies 23,26,35,36 , pertaining to jumping performance:…”
Section: Data Processing and Outcome Measuresmentioning
confidence: 99%
“…The minimum load (L1) was 14 kg for all subjects (mass of the unloaded Smith machine barbell), and the 85% of 1RM was the maximum load (L6). The 4 intermediate loads were equidistantly distributed between L1 and L6 (L2 = 25.7 ± 2.8 kg, L3 = 37.2 ± 4.3 kg, L4 = 48.4 ± 6.5 kg, and L5 = 59.9 ± 8.7 kg) (11). During the sessions where the L-V relationship was established using the multiple-point method, 6 loads (L1-L2-L3-L4-L5-L6) were applied, whereas only L1 and L6 were applied in a consecutive fashion in sessions where the 2-point method was used.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth highlighting that in all previous studies, the 2-point method was extracted from a testing procedure based on the multiple-point method. To date, only García-Ramos et al (11) and Fessl et al (4) shown that the 2-point method applied in field conditions (i.e., only 2 loads are used during the testing procedure) is generally reliable and valid with respect to the multiple-point method to assess maximal neuromuscular capacities through the F-V relationship in the leg cycle ergometer and squat jump exercises, respectively. However, the reliability and validity of the 2-point method applied in field conditions to obtain the L-V relationship variables have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%